Une analyse bibliométrique pour éclairer la mise à l’agenda scientifique des « services environnementaux » - Philippe Jeanneaux; Olivier Aznar; Sybille de Mareschal (VertigO, 2012)
Publication in academic journals is a good way to assess the emergence and the development concerning a new paradigm like services linked with environment ("ecosystem services", "ecological services", "environmental services"). Our bibliometric study of the Web of Science (Thomson Reuters) database highlights the intensive scientific work about these ecosystem or environmental services and suggests the existence of a research frontier. The analysis distinguishes ecosystem service, used by from environmental service which is more used by the social sciences.